Dental Trauma at a University Dental Clinic in Milan including the SARS-CoV-2 Period - Sara Pederielli; Cristina Mirelli; Federico Pozzi; Aldo Bruno Giannì; Roberto Biagi (Dentistry Journal, 2021)
The aim of this study i.e., is to present the distribution of traumatic dental injuries (TDI) in 306 patients registered at the Unit of Dental Emergencies at a University Dental Clinic in Milan, Italy, between June 2019 and May 2021. This time frame includes the beginning of the SARS-CoV-2 pandemic. Information regarding age, gender, number and type of injured teeth, type of traumatic injury, and data on where or how the injury happened were recorded. Seventy-nine percent of patients can be classified as pediatric (under 14 years old), and in all age groups, male patients were found to be more susceptible (1.6:1). A total of 480 teeth were involved, 59% of which were deciduous, and 41% permanent. The most affected teeth in both dentitions were upper central incisors. In deciduous teeth, periodontal lesions were more common, whereas in permanent dentitions, dental fractures were diagnosed more often. Most data found in this study confirms the results found in the literature. The biggest difference, due to changes in daily routine during the SARS-CoV-2 pandemic, can be found by analyzing the incidence and etiology. As a matter of fact, there was a decrease in school accidents, whereas domestic falls remained constant.